Optical properties of single‐walled carbon nanotubes filled with CuCl by gas‐phase technique. Issue 12 (11th September 2014) - Fedotov, Pavel V.; Tonkikh, Alexander A.; Obraztsova, Ekaterina A.; Nasibulin, Albert G.; Kauppinen, Esko I.; Chuvilin, Andrey L.; Obraztsova, Elena D.
<x xml:space="preserve">Abstract</x> Single‐walled carbon nanotubes (SWCNTs) have unique electronic and optical properties, which are attractive in various applications. These properties can be further improved by functionalization. In this work, it is shown that filling nanotubes with CuCl leads to improvement of their electro‐conductive and optical transmission properties up to outstanding level. The improvement is due to the significant p‐type doping of the functionalized nanotubes. That leads to a huge increase in nanotubes charge carrier density and the considerable decrease of the nanotubes absorption via Pauli blocking. The functionalization was realized via a gas‐phase filling of SWCNTs with CuCl. We demonstrate the effect of huge doping on optical properties of nanotubes with different average diameters. The observed sufficient stability of the CuCl@SWCNT composite is proved to be due to the formation of quasi‐one‐dimensional (1D) CuCl crystal inside nanotubes. <inline-graphic xlink:href="ark:/27927/pgh2jcbhknm" content-type="pssb201451240-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> AC‐HRTEM image of 1D CuCl crystal formed inside SWCNT.